PENGARUH SUHU PENGERINGAN YANG BERBEDA TERHADAP KUALITAS CABAI RAWIT (Capsicum frutescens L.) - Evi Ari Parfiyanti; Rini Budi Hastuti; Endah Dwi Hastuti (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2016)
Chili pepper has a high economic value but it belongs to the type of fruit that can easily damage because of the climacteric phase, therefore, it is needed a proper postharvest handling, either by drying with different temperatures for 14 hours. The research objective is to find out the effect of drying temperature for the quality of chili pepper and find out the best drying temperature that influences the quality of chili pepper. The research design that used is completely randomized design (CRD) with three replications. The drying temperatures that use are T1 (50°C), T2 (60°C) and T3 (70°C). The research parameter consists of weight loss, water content, vitamin C and discoloration. Methods of analyzing the data that used is analysis of variance (ANOVA) continued by significant different test of Duncan Multiple Range Test (DMRT) at the 95% signification level. The chili pepper that drainaged in temperature of 50°C can shows the best result for defend of chili pepper color and texture. The highest contens of vitamin C can be found in temperature of 50°C that show the number of 63.287 mg%. The drying temperature of 70°C give the highest weight loss that show the number of 3.833% and give the lowest water content for about 72.4%. The research of study show that the drying temperature influence the alteration of chili pepper quality which show the result that it can decrease the fruit weight loss, the water content of chili pepper, vitamin C contens and also the color and the texture of chili pepper.Keywords: Chili pepper, drying temperature, weight loss, water content, vitamin C